Occurrence of plant-uncoupling mitochondrial protein (PUMP) in diverse organs and tissues of several plants - Jezek, P; Zácková, M; Kosarová, J; Rodrigues, E T; Madeira, V M; Vicente, J A (Journal of bioenergetics and biomembranes, 2000)
The presence of plant-uncoupling mitochondrial protein (PUMP), previously described by Vercesi et al. (1995), was screened in mitochondria of various organs or tissues of several plant species. This was done functionally, by monitoring purine nucleotide-sensitive linoleic acid-induced uncoupling, or by Western blots. The following findings were established: (1) PUMP was found in most of the higher plants tested; (2) since ATP inhibition of linoleic acid-induced membrane potential decrease varied, PUMP content might differ in different plant tissues, as observed with mitochondria from maize roots, maize seeds, spinach leaves, wheat shoots, carrot roots, cauliflower, broccoli, maize shoots, turnip root, and potato calli. Western blots also indicated PUMP presence in oat shoots, carnation petals, onion bulbs, red beet root, green cabbage, and Sedum leaves. (3) PUMP was not detected in mushrooms. We conclude that PUMP is likely present in the mitochondria of organs and tissues of all higher plants.
Keywords: Plants; Mitochondria; Uncoupling Protein 1; adenosintrifosfát; Uncoupling Agents; druhová specificita; iontové kanály; Oxygen Consumption; tkáňová distribuce; Linoleic Acid; Membrane Potential, Mitochondrial; rozpřahující látky; mitochondrie; Mitochondrial Proteins; mitochondriální proteiny; kyselina linolová; uncoupling protein 1; Adenosine Triphosphate; Tissue Distribution; rostlinné proteiny; spotřeba kyslíku; Species Specificity; Plant Proteins; Ion Channels; membránový potenciál mitochondrií; rostliny